Modeling Chinese stock returns with stable distribution - Xu, Weidong; Wu, Chongfeng; Dong, Yucheng; Xiao, Weilin (Mathematical and computer modelling, 2011)
In this paper we demonstrate that an α -stable distribution is better fitted to Chinese stock return data in the Shanghai Composite Index and the Shenzhen Component Index than the classical Black–Scholes model. The sample quantile method developed by McCulloch [J.H. McCulloch, Simple consistent estimators of stable distribution parameters, Communications in Statistics-Simulation and Computation 15 (4) (1986) 1109–1136] is used to estimate the α -stable distribution for the Shanghai Composite Index and the Shenzhen Component Index. The empirical results show that the asymmetric leptokurtic features presented in the Shanghai Composite Index and Shenzhen Component Index returns can be captured by an α -stable law.